The Relationship Between Mathematical Resilience and Critical Thinking Ability of Student - Salma Hasna Arumaisya; Tina Sri Sumartini (PRISMA, 2026)
Critical thinking ability is one of the important abilities in mathematics learning, while mathematical resilience acts as an affective factor that encourages students to persevere in the face of difficulties. This study aims to analyze the relationship between mathematical resilience and students' critical thinking skills in the context of mathematics learning. The research method used a correlational quantitative approach involving 20 Al-Hikmah Junior High School students as samples. Data were collected through mathematical resilience questionnaire and mathematical problem-based critical thinking ability test, then analyzed using correlation test (Pearson/Spearman) and crosstab test. The results showed that there was no significant relationship (r = 0.266 < 0.05) between mathematical resilience and critical thinking ability. This finding indicates that other factors, such as learning motivation, teaching model, or learning environment, may have more influence on students' critical thinking ability. Nonetheless, this study contributes to the understanding of students' cognitive and affective abilities in the context of mathematics learning.